Hedychium coronarium and Zingiber officinaleFresh rhizomeextracts for the biocontrol of the parasitic larvae Anopheles gambiae - Yadav, Neelima; Chandel, Saket Singh; Pande, Vipin B; R Manapure, Sharad; Venkatachalam, T. (Journal of Neonatal Surgery, 2025)
Purpose: This study investigated the biocontrol potential of Hedychium coronarium and Zingiber officinale fresh rhizome extracts against Anopheles gambiae larvae. Materials and Methods: An. gambiae larvae were tested against fresh rhizome extracts of H. coronarium and Z. officinale at varying doses (25, 50, 100, and 200 mg/ml) for 24 and 48 hours. Probit analysis was used to calculate lethal concentrations (LC50 and LC90) and evaluate mortality and emergence inhibition. The one-way ANOVA and Tukey's post-hoc test (p<0.05) were used to assess the statistical significance of the differences between the control and treatment groups. Result and Discussion: The findings demonstrated that both extracts increased larval mortality in a dose-dependent manner. At 24 hours, the LC90 values were 1580.32 μg/ml and 1720.45 μg/ml, respectively, whereas the LC50 values were 1185.42 μg/ml (H. coronarium) and1270.25 μg/ml (Z. officinale). The LC50 and LC90 values decreased after 48 hours, suggesting that the product became more effective over time. Additionally, inhibition of emergence (IE%) was noted, with Z. officinale exhibiting a somewhat lower inhibition rate than H. coronarium. Significant differences between the treatment and control groups were confirmed by statistical analysis (p<0.05). The larvicidal effect of the plants may be due to presence of alkaloids, flavonoidsand essential oils by their inference with larval metabolism and brain function. Conclusion and Recommendation: The potential of extracts from Z. officinale and H. coronarium as natural larvicides against An. gambiae is confirmed by the study. An environmentally beneficial substitute for synthetic pesticides is provided by these extracts. Future studies should look into formulation optimisation, field applications, and the metabolic processes that underlie their toxicity.